Meanings of Poetry in The Classical Book Ta’līmu Al-Muta’allim by Burhānuddīn Az-Zarnūji (A Study of The Levels of The Roman Ingarden Norms) - M. Ibnu Nafiudin; Imam Makruf (Arabic Literature Department, 2021)
This research aims to describe the structure of the text and the meaning of the poetry on the book Ta'līmu Al-Muta'allīm by Burhānuddīn Az-Zarnūji. This research will be analyzed through structural and Roman Ingarden's strata of norm approach which reveals about educational values. This descriptive qualitative research employs observation and note technique as a method of data collection, in which the researcher records data in the form of verses in the Ta'līmu Al-Muta'allīm book, especially those in chapter 5. The poetry data found, is analyzed by using data triangulation. The results of the research show that the text structure of the poetry of the book Ta'līmu Al-Muta'allīm by Burhānuddīn Az-Zarnūji consists of five layers, including 1) sound layer, 2) meaning layer, 3) layers of things that are stated, 4) the world layer, and 5) the metaphysical layer. Meanwhile, the educational values contain in the meaning of the poetry include the values of religious education, the values of moral education, the values of social education, the values of cultural education, and the values of aesthetic education.